Advanced Research on Dopamine Signaling to Develop Drugs for the Treatment of Mental Disorders: Ser311Cys Polymorphisms of the Dopamine D2-Receptor Gene and Schizophrenia - Masanari Itokawa; Tadao Arinami; Michio Toru (Elsevier, 2010)
Schizophrenia is a debilitating and complex mental disorder with a prevalence of approximately 1% worldwide. The etiology remains unclear, despite massive research efforts. Hyperactive dopaminergic signal transduction in the central nervous system is suggested to be involved in the pathophysiology of schizophrenia (the dopamine hypothesis). The dopamine D2-receptor (DRD2) gene is thus a promising candidate for associations with risk of schizophrenia. We investigated DRD2 and found a novel missense nucleotide change causing an amino acid substitution of serine with cysteine at codon 311 (Ser311Cys). We performed an association study using 156 schizophrenia patients and 300 controls. Cys311 in DRD2 was significantly associated with schizophrenia. Patients with the Cys311 allele displayed shorter duration of hospitalization and less severe negative symptoms and were more frequently married compared to patients without this allele, suggesting good response to treatment. We expanded samples to 291 patients with schizophrenia (including 11 postmortem brain samples), 579 controls, and 78 patients with affective disorders in a further case-control study. Cys311 was associated with schizophrenia, particularly in patients without negative symptoms, and bipolar disorder with mood-incongruent psychotic symptoms. Three meta-analyses using over 20 published studies confirmed the association. In vitro studies showed that Cys311-type D2 receptor impairs dopamine-induced sequestration, which appears to be consistent with the dopamine hypothesis. Keywords:: schizophrenia, dopamine D2 receptor, association, Ser311Cys, sequestration